EFEKTIVITAS PENGGUNAAN E-BOOK DALAM KETERAMPILAN MEMBACA KRITIS BAGI MAHASISWA TINGKAT AWAL - Saputra, Desma Yuliadi; Andriani, Rina; Subroto, Desty Endrawati (Teks: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
Critical thinking skills are essential competencies that students must master in the global era, which is filled with challenges. One of the rapidly growing educational media is the E-book, offering high flexibility and interactivity to support independent learning. This study aims to examine the effectiveness of E-book usage in enhancing critical reading skills among early-year students. The research employs a quasi-experimental method with a pre-test and post-test design applied to two groups: a control group using printed books and an experimental group using E-books. Data were collected through critical reading ability tests and student participation questionnaires. The results indicate that students using E-books showed a significant improvement in critical reading skills compared to the control group. Additionally, E-books were found to increase reading interest and student engagement in the learning process through interactive features provided. However, challenges such as access to digital devices and technological literacy remain. Therefore, appropriate strategies are needed to optimize E-book use as a learning medium in higher education. The findings of this study are expected to serve as a reference for developing relevant curricula in the digital era and strengthening the integration of technology in the learning process.